Nurse-delivered interventions for mental health in primary care: a systematic review of randomized controlled trials. (26th October 2018) - Halcomb, Elizabeth Jane; McInnes, Susan; Patterson, Christopher; Moxham, Lorna
Abstract: Background: Mental health issues are increasingly prevalent within the community. Many people experiencing mental health issues have established relationships with primary care providers, including general practice nurses (GPNs). With the recent growth of general practice nursing, it is timely to explore the evidence for GPNs to provide mental health interventions for adults with mental illness within their scope of practice. Objective: To synthesize the evidence about nurse-delivered interventions in primary care for adults with mental illness. Methods: A systematic review of randomized control trials (RCTs) retrieved from the CINAHL, Ovid MEDLINE and EBSCO electronic databases between 1998 and 2017. Results: Nine randomized controlled trials were identified, which reported nurse-delivered interventions in primary care for the management of mental health in adults with mental illness. The heterogeneity of interventions and outcomes made comparison of studies difficult. Seven studies demonstrated significant improvement in at least one outcome following the intervention. In some studies, these improvements were sustained well beyond the intervention. Additionally, consumers were satisfied with the interventions and the role of the GPN. Conclusion: There is currently limited evidence of the impact of nurse-delivered interventions in primary care for adults with mental illness. Given the significant improvements in symptoms and the acceptability of interventions seen in included studies, there is a need for further robust research exploring the role of the GPN both individually and within the multidisciplinary team. Such research will enable stronger conclusions to be drawn about the impact of nurse-delivered interventions in primary care for adults with mental illness.